Kewenangan Badan Koordinasi Penanaman Modal Pasca Berlakunya OSS - Santhy Ainun Adrianty; Lydia Goutama; Nadya Rizky Nakayo (Faculty of Law Hang Tuah University, 2019)
Government Regulation Number 24 regulates business licensing by integrating electronic system or Online Single Submission (OSS). In the implementation of the OSS system, it still faces many obstacles. The existence of Government Regulation Number 24/2018 tends to violate Law Number 25 of 2007 (hereinafter referred to as the Investment Act) concerning Investment because it was allegedly that the OSS institution took over the authority of the Investment Coordinating Board (BKPM) while the Investment Law states that investment licensing is the domain of BKPM. This results in a contradiction in the principle of Lex Superior Derogat Legi Inferior, where the principle states that lower regulations (PP) may not conflict with higher regulations (the Investment Law). In addition to the contradictions in the laws and regulations, OSS also still faces another obstacle, which is the lack of OSS infrastructure, so that the purpose of accelerating licensing services cannot be optimally implemented.